HUBUNGAN ANTARA OBESITAS, POLA MAKAN, AKTIFITAS FISIK, MEROKOK DAN LAMA TIDUR DENGAN KEJADIAN HIPERTENSI PADA LANSIA (Studi Kasus di Desa Limbung Dusun Mulyorejo dan Sido Mulyo Posyandu Bunda Kabupaten Kubu Raya) - Gusti, Fany Ilyasa; Ridha, Abduh; Budiastutik, Indah (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak, 2015)
Data from WHO in 2011 showed that hypertension lead to 8 million deaths per year worldwide and 1.5 million deaths per year in the region of Southeast Asia. On the other hand, integrated surveillance data of Kabupaten Kubu Raya in 2013 indicated that the number of hypertension cases in elderly ( 45-69 years old) was 2539 cases (38%). Meanwhile, as many as 20% elderly in Desa Limbung Dusun Mulyo Rejo and Sidomulyo got hypertension each month (Posyandu Bunda, 2013)This study aimed at figuring out the correlation of obesity, eating pattern, physical activity, sleep duration, and hypertension in elderly in Desa Limbung Dusun Mulyorejo and Sido Mulyo, Posyandu Bunda Kabupaten Kubu Raya. An observational analytic, as well as a cross sectional approach, was carried out in this study. The population were 50 elderly from Desa Limbung Dusun Mulyorejo and 100 elderly from Dusun Sidomulyo. The study revealed two findings. First, there were correlation of preventive eating pattern (p value=0,000; OR=36,833), triggered eating pattern (p value=0,009; OR=3,529), physical activities (p value=0,002;OR=4,449), smoking habit (p value=0,012; OR 4,504), and hypertension cases in elderly in Desa Limbung Dusun Mulyorejo and Sido Mulyo, Posyandu Bunda Kabupaten Kubu Raya. Second, there were no correlation of obesity (p value=0,119), sleep duration (p value=0,458) and hypertension cases in elderly in Desa Limbung Dusun Mulyorejo and Sido Mulyo, Posyandu Bunda Kabupaten Kubu Raya.As a result, health department of Kabupaten Kubu Raya should cooperate with Puskesmas Sungai Durian and Posyandu Bunda to conduct more socialization and counseling on the hypertension risks. They also should encourage the respondents to exercise regularly and consume healthy food and avoid taking food which can trigger hypertension.Keywords: obesity, eating pattern, smoking, sleep duration, and hypertension.